Relationships between daily mood states and real-time cognitive performance in individuals with bipolar disorder and healthy comparators: A remote ambulatory assessment study. Issue 8 (14th September 2021) - Bomyea, Jessica A.; Parrish, Emma M.; Paolillo, Emily W.; Filip, Tess F.; Eyler, Lisa T.; Depp, Colin A.; Moore, Raeanne C.
ABSTRACT: Objective: Neuropsychological impairments are observed in individuals with Bipolar Disorder (BD), yet knowledge of how cognitive deficits unfold in real-time remains limited. Given intraindividual variability in mood observed in people with BD, and the potential for mood and cognition to be mutually influential, we employed ambulatory assessment technologies to examine potential contemporaneous (same survey) and lagged (next survey) relationships of congition and mood. Methods: Outpatients with BD (n = 46) or no psychiatric disorders (heathy volunteers [HV]; n = 20) completed in-laboratory neurobehavioral assessments and 14 days of smartphone-administered mobile cognitive tests and ratings of affective variables. Linear mixed-effects models were used to analyze real-time relationships between mobile cognitive test performance and mood. Results: On in-laboratory tests, participants with BD showed worse cognitive performance than HVs as well as mild depression severity; mood and cognitive performance were unrelated. On mobile cognitive tests and surveys, participants with BD showed somewhat worse cognitive performance and ratings of lower energy and greater sadness relative to HV participants. Among those with BD, mania and sadness earlier in the day related to worse processing speed and better working memory performance, respectively, on the next survey. In contrast, same survey ratings of greater stress related to better working memory, and greater happiness related to better processing speed. Conclusions: Real-time assessments of mood and cognition provide incremental information beyond what can be gleaned from laboratory assessments. Understanding how these affect-related changes in processing speed emerge and play out in daily life may provide clinically useful information for treatment planning.